Sensitivity analysis and material identification for activated smooth muscle - Rohan, Eduard; Cimrman, Robert (Computer Assisted Methods in Engineering and Science, 2023)
The paper deals with the problem of material identification for smooth muscle tissue in activated, or passive states. In [17] a composite type mathematical model has been proposed describing the complexity of the tissue reduced to the networks of muscle and collagen fibres. The computational model is based on the total Lagrangian formulation with incompressibility of the bulk material. The problem of inflating vessels is considered in order to allow simulation of real experimental conditions and, thus, to determine constitutive parameters of muscle in active state. These parameters are identified also from hysteresis, or relaxation curves. The direct differentiation, or the adjoint systems techniques are applied to the sensitivity analysis. Results of numerical tests are given.